The Development of Ḥadīth in 9th Century Andalusia: A Study of Al-Bida’ Wa Al-Nahy ‘Anhā by Ibn Waddah Al-Qurtubi - Achmadana Syachrizal M. F; Ananda Prayogi; Muhid Muhid; Andris Nurita; Maghza Rizaka (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Based on data presented by ‘Abd al-Razzāq, out of 60 ḥadīth studies spanning from 1986 to 2004, only five focused on the Andalusian region, accounting for approximately 8.3%, with none specifically addressing areas in Andalusia. More specifically, there is no connection found with the study of ḥadīth that centers on researching the figure of Muhammad Ibn Waḍḍāh (d. 899) in his book titled al-Bida’ wa al-Nahy ‘Anhā. The purpose of this writing is to explore the biography and scholarly journey of Ibn Waḍḍāh, as well as to delve deeply into related backgrounds, systematics, and methods employed in the preparation of the book al-Bida’ wa al-Nahy ‘Anhā. The method employed in this article is qualitative, utilizing a library study approach, given that the desired data is narrative and extracted from written literature. The article concludes that the background of composing the book is influenced by socio-political conditions favoring Ibn Waḍḍāh as a scholar dedicated to global knowledge. The socio-cultural conditions were alarming, marked by phenomena such as cultural acculturation, interfaith marriages, and massive conversions to Islam, prompting Ibn Waḍḍāh (d. 899) to react to the degradation of faith at that time.